Answer:
The sixteenth term is
.
Explanation:
Given,
![a_1=x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ygpkork997v5urb2sz58euv6gvbkljqi1e.png)
![a_3=y](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b83mcyj0vy75w1e1skww3lnhvxheue8w2r.png)
And also given,
![T_n=a+(n-1)d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cvfab4lgxp97s5bendw7p72gu8e4tvow44.png)
We have to find out the 16th term of given A.P.
Firstly, we will find out the common difference(d).
Common difference(d) is calculated by given formula.
![T_3=a+(n-1)d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/638mzkzwcuvou0ppz2p7xpxxivvm9lg439.png)
On putting the values, we get;
![y=x+(3-1)d\\\\y=x+2d\\\\2d=y-x\\\\d=(y-x)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6qvyfpwwghr1uj2e2ig427speyy5awgrm9.png)
Now the value of 'd' is calculated, so we can find out the 16th term by using the formula.
![T_(16)=x+(16-1)(y-x)/(2)\\\\T_(16)=x+15*(y-x)/(2)\\\\ T_(16)=x+(15(y-x))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r0dwyt7sruhspjkabspbc403g42quqcyzt.png)
Hence The sixteenth term is
.